EFEKTIVITAS PENAMBAHAN VITAMIN A DAN ZAT BESI PADA GARAM YODIUM TERHADAP STATUS GIZI DAN KONSENTRASI BELAJAR ANAK SEKOLAH DASAR - M. Saidin; Muherdiyantiningsih Muherdiyantiningsih; Endi Ridwan; Nur Ihsan; Astuti Lamid; Sukati Sukati; Lies Karyadi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
THE EFFECT OF VITAMIN A AND IRON ADDED INTO IODIZED SALT ON NUTRITION STATUS AND LEARNING CONCENTRATION OF ELEMENTARY SCHOOL CHILDREN.Background: It was assumed that in some areas of Indonesia previously recognized as area of endemic goitre, thenutrition problem in that area became more complex due to crisis of economy. Probably some people in that area not only suffering from 100 but also vitamin A and iron deficiency. In this condition intervention of multinutrient is more reasonable than of single nutrient in improving nutrition status.Objectives: The aim of this study was to investigate the effect of vitamin A and iron added into iodized salt on iodine status and learning concentration of elementary school children in moderate endemic goiter area.Methods: The study design was "field trial". Study sites covered two subdistricts, namely Nagak subdistrict and Pelabuhan ratu subdistrict of Sukabumi District, West Java. A total of 221 boys and girls students in the fourth, fifth and sixth grades with positive goitre at grade I, by palpation were randomly assigned into four groups. Each group received different treatment. Group I received iodized salt (43 ppm of Iodine) + 180 ppm of vitamin A (A formula), group II received iodized salt (52 ppm) + 1500 ppm of iron (8 formula), group III received iodized salt only (37 ppm) (C formula) and group IV received iodized salt only (20 ppm). Data evaluation was collected 18 week after intervention.Results: The result of study revealed that proportion of goitre measured by palpation decreased in all groups, group I (14%), group II (7%), group III (21%) as well as group IV (19%). The increment of serum tetraiodotirosine (thyroxine) hormone (T4) of group II (5.02 ug/dl) and group I (4.60 ug/dl) were significantly higher than that of group Ill (2.04 ug/dl) or group IV (2.91 ug/dl). There were no significant differences in the increment of serum triiodotirosine hormone (T3) among group. The haemoglobin level of group II increased (0.36 g/dl), while group I and group IV were slightly decreased. The proportion of student suffering from anemia in group I decreased (25%), while in the other groups increased (4.3% to 9.8%).Conclusions: The increment of T4 was not followed by improvement of learning concentration measured by using 'Weschler Intelligence Scale for Children" method.Keywords: 100 (Iodine deficiency disorder), nutrition status; iodine status; learning concentration; endemic goitre area; palpation; tetraiodotirosine (thyroxine); triiodotirosine; Weschler Intelligence Scale for Children".